Serodiagnosis of Recently Acquired Toxoplasma gondii Infection Using an Enzyme-Linked Immunosorbent Assay with a Combination of Recombinant Antigens - Li, Shuli (American Society for Microbiology, 2000)
An enzyme-linked immunosorbent assay (ELISA) using four recombinant antigens of Toxoplasma gondii (rP22, rP25, rP29, and rP35) was used in an attempt to differentiate pregnant women with toxoplasma serologic profiles (TSPs) indicative of recently acquired infections (acute profile) from those with TSPs indicative of infections acquired in the distant past (chronic profile). In general, immunoglobulin G antibodies in sera from women with the acute profile reacted more strongly with the recombinant antigens than did those in sera from women with the chronic profile. However, reactivities differed significantly between antigens that reacted with a single serum and between sera that reacted with a single antigen. Because of these variations, we employed a combination of the four antigens in an ELISA (Comb-ELISA) and evaluated its ability to distinguish pregnant women with the acute profile from those with the chronic profile. Eighteen of 20 (90%) sera from acute-profile women were positive in the Comb-ELISA, whereas 69 of 70 (98.6%) sera from the chronic-profile women were negative. Thus, the Comb-ELISA may be useful for diagnosis of toxoplasmosis in pregnant women and for differentiation between recently acquired infections and infections acquired in the more distant past.